Tax instruments of local budget revenue regulation - Sukach, O.; Sarana, L.; Gordienko, L. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2021)
The decentralization of finance in the context of reform of local self-government in Ukraine needs the improvement of the tax system i.e. the optimal allocation of taxes between the local and state budgets. The purpose of this research is to enhance the existing experience of budget decentralization with the identification of the practical results of the decentralization reform and its impact on the local territorial communities in Ukraine. The article examines and summarizes the current experience of budget decentralization in Ukraine and the results of the reform, as well as their community impact. The main focus of the study is on the principles of tax policy implementation in terms of taxes and fees credited to local budgets. The purpose of the study is to optimize the tax mechanisms for filling local budgets in Ukraine. The article examines the state of filling local budgets and its impact on socio-economic development of the community. It is determined that the basis of revenues are tax revenues, the share of which is growing every year. The reform resulted in increased interest of local governments in increasing revenues to local budgets, finding reserves to fill them, improving the efficiency of administration of taxes and fees. Thus, the main budget-forming tax is the personal income tax, which in the amount of 60 percent is credited to the budgets of rural, township, urban territorial communities. In its turn, the positive dynamics is the reduction of intergovernmental transfers. Increasing the dependence of local budgets on personal income tax and own local taxes is a positive consequence of the implemented budget reform. According to the results of the study, the directions of optimizing the use of tax instruments in filling local budgets are substantiated. One of the crucial conditions for creating a highly developed market economy is the formation of local self-government as an effectively functioning part of the public sector.